Emergency situations with explosions of ammunition: patterns of occurrence and progress - Иванов, Евгений Владимирович; Лобойченко, Валентина Михайловна; Артемьев, Сергей Робленович; Васюков, Александр Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2016)
Results of studies of the main causes and patterns of occurrence and progress of man-made emergency situations (MMES) with explosions of ammunition are summarized. The analysis of records on 73 MMES with explosions of ammunition is performed. The major causes and patterns of occurrence of MMES are identified. It is shown that the vast majority of emergencies is caused by a human factor, namely safety violation. May, June and October are the most riskful months. MMES should be seen as a complex system with specific, new properties such as significant duration, spatial factor and scale factor, which are not inherent in its elements - cartridges. For example, the mercury content in the cartridge primer showed that the scale factor can turn the shot of minor environmental effect into the catastrophic impact of MMES with explosions of ammunition on the environment.